Effect of different anthelmintic drugs on the development and efficacy of Duddingtonia flagrans - Zegbi, Sara (2024)
Nematophagous fungi are a biological control tool used against gastrointestinal nematodes in livestock. These fungi prey on free-living larvae in faeces and could be affected by active drugs excreted post-treatment. This study aimed to determine in vitro and under environmental conditions the effect of the following anthelmintics on the fungus Duddingtonia flagrans: ivermectin, levamisole, albendazole, fenbendazole and ricobendazole. The in vitro effect of anthelmintics on fungal growth and predatory capacity was assessed in corn meal agar and coprocultures, respectively. Ivermectin (1, 2 and 10 ppm), fenbendazole (0.027, 0.054 and 1 ppm) and albendazole (1 ppm) significantly affected fungal development. The fungal efficacy against L3 was high in the control and levamisole coprocultures but decreased significantly in the presence of albendazole, fenbendazole, ricobendazole and ivermectin. The impact of levamisole on D. flagrans was further assessed under environmental conditions in autumn and winter; the fungal efficacy measured in faecal pats and the surrounding herbage was not affected by levamisole at any time. This study shows that using albendazole, fenbendazole, ricobendazole or ivermectin may compromise fungal activity, as these drugs affect the free-living stages of nematodes in faeces, but levamisole can be safely considered in parasite control strategies involving D. flagrans and anthelmintic treatments.